PP.29.11: EDUCATIONAL LEVEL INFLUENCE IN THE PREVALENCE, AWARENESS, TREATMENT AND CONTROL OF HYPERTENSION IN COLOMBIA. (June 2015) - Jaramillo, P. Lopez; Lopez, P.A. Camacho; Arbelaez, D. G.ó.mez; Alvarado, L.; Molina, D.I.; Sanchez, G.; Arcos, E.; Narvaez, C.; Garcia, H.; Perez, M.; Cañon, W.; Cure, C.; et al.
Abstract : Objective: To assess the relation of the education level in prevalence, awareness, treatment and control of hypertension in Colombia. Design and method: Cross-sectional study with longitudinal component. All participants were selected from urban and rural communities within 11 of Colombia[Combining Acute Accent]s departments. Households were eligible if at least one member was 35 to 70 years-old and if the members intended to continue living at that address for another 4 years or more. Data was entered into the iDATAfax® system. Data analysis was performed by using STATA/SE 12. Results: A total of 21390 individuals were selected for the survey. Of these, 7444 individuals aged 35 to 70 years were eligible from 58 communities, of which 49.5% were in rural areas and 64% were female. The mean age was 50.81 ± 9.75 years-old. 21.9% never attended school and 33.9% had a high-school or higher level of education. The prevalence of hypertension (HTA) was 36.7% [95% CI: 35.6 - 37.8%]. The highest prevalence of HTA was in the Pacific region 40.5% and the lowest was in the Amazonian region 25.6% (p < 0.001). The prevalence, awareness, treatment and control of HTA showed significant trends by educational level (p < 0.001) (Figure). Higher education was associated with a lower prevalence of HTA in younger and older age groups (p = 0.005), women (p < 0.001) but no men, urban and rural (p < 0.001) and in specific regions (Atlantic, Central, Amazonian, p < 0.05). Higher education was associated with awareness, treatment and control in men and rural areas only (p < 0.05). Figure. No caption available. Conclusions: Hypertension is highly prevalent in Colombia as previously reported in other Latin America countries. The low level of awareness, treatment and control is related with low educational level and rural communities. The significant regional differences in these factors, suggests the need to develop region-specific strategies to achieve the desired improvements in detection and control.